2014
DOI: 10.1016/j.mrfmmm.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Illegitimate V(D)J recombination-mediated deletions in Notch1 and Bcl11b are not sufficient for extensive clonal expansion and show minimal age or sex bias in frequency or junctional processing

Abstract: Illegitimate V(D)J recombination at oncogenes and tumor suppressor genes is implicated in formation of several T cell malignancies. Notch1 and Bcl11b, genes involved in developing T cell specification, selection, proliferation, and survival, were previously shown to contain hotspots for deletional illegitimate V(D)J recombination associated with radiation-induced thymic lymphoma. Interestingly, these deletions were also observed in wild-type animals. In this study, we conducted frequency, clonality, and juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…Clonal expansion of cells with LOH at the Bcl11b locus has been reported as being one of the earliest detectable changes (along with Myc amplification) in the thymus post-irradiation but prior to the onset of lymphoma [ 37 ]. The presence of Notch1 Type 1 deletion-bearing cells in the normal mouse thymus [ 38 ] suggests that activating Notch1 deletions in the TL could result from selective expansion of cells with pre-existing spontaneous deletions, yet other evidence indicates that the recombination-mediated deletions are a later spontaneous event in the carcinogenic sequence [ 37 , 39 ], with no increase in deletion frequency in TL from irradiated compared to unirradiated mice [ 31 ]. Since studies of large panels of T-ALL have failed to find equivalent recombination-mediated deletions in the human NOTCH1 gene [ 32 ], this represents a mouse-specific tumour susceptibility that may contribute to their increased vulnerability to radiation-induced T cell tumours; though, the finding of a NOTCH1 Type 2 activating deletion (not recombination mediated) in a T-ALL patient [ 40 ] demonstrates that the mechanism has prima facie relevance to human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal expansion of cells with LOH at the Bcl11b locus has been reported as being one of the earliest detectable changes (along with Myc amplification) in the thymus post-irradiation but prior to the onset of lymphoma [ 37 ]. The presence of Notch1 Type 1 deletion-bearing cells in the normal mouse thymus [ 38 ] suggests that activating Notch1 deletions in the TL could result from selective expansion of cells with pre-existing spontaneous deletions, yet other evidence indicates that the recombination-mediated deletions are a later spontaneous event in the carcinogenic sequence [ 37 , 39 ], with no increase in deletion frequency in TL from irradiated compared to unirradiated mice [ 31 ]. Since studies of large panels of T-ALL have failed to find equivalent recombination-mediated deletions in the human NOTCH1 gene [ 32 ], this represents a mouse-specific tumour susceptibility that may contribute to their increased vulnerability to radiation-induced T cell tumours; though, the finding of a NOTCH1 Type 2 activating deletion (not recombination mediated) in a T-ALL patient [ 40 ] demonstrates that the mechanism has prima facie relevance to human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We then observed that Bcl11b cryptic rearrangements were also detectable in two Tg endoR2 −/− animals induced by TAM, albeit approximately 10 times less frequently than in WT [(33, 37); Figure 4B; Table 2]. Such cryptic rearrangements were not detected in the 1 million cells equivalent DNA tested for the third Tg endoR2 −/− TAM + animal (Figure 4).…”
Section: Resultsmentioning
confidence: 89%
“…We used fluctuation PCR of total thymocytes DNA to assess frequencies of Bcl11b recombination which was similar in WT (25 rearrangements per million thymocytes) and RAG-competent Tg animals (27.7 rearrangements per million thymocytes), and in the range of frequencies documented previously [23–50 rearrangements per million thymocytes in Ref. (37) and Ref. (33), respectively; data not shown].…”
Section: Resultsmentioning
confidence: 92%